Metode dan corak Tafsir Al-Qur’an: Tahlili, Ijmali, Muqaran, dan Maudhui - Masu’ud, Naufal Alfarizi; Faisol, Faisol; Alqadir, Arifin; Kamaludin, Kamaludin; Azis, Akhmad Fahrul (Maliki Interdisciplinary Journal, 2024)
We need to understand the Koran precisely and accurately as a guide. Humanity has always tried to understand the Qur’an, especially Mufasir. This has given rise to a methodology for interpreting the Qur’an which consists of various types of interpretation methods. This article explains four different ways of interpreting the Al-Aqran. The four methods are tafsir ijmali (global), tafsir tahlili (analytical), tafsir maudhu’i (thematic), and tafsir muqaran (comparative). Each of these methods will be discussed one by one, including definitions, advantages and disadvantages, as well as examples of interpretation results. For this reason, this article adopts a literary research method with a philosophical approach.